Juries and the transformation of criminal justice in France in the nineteenth & twentieth centuries - Donovan, James M. (James Michael), 1948- (Studies in legal history., 2010)
Donovan takes a comprehensive approach to the history of the jury in modern France by investigating the legal, political, sociocultural, and intellectual aspects of jury trial from the Revolution through the 20th century. Challenging the contention of modern historians that the generally bourgeois jurors of 19th-century France usually rendered verdicts in keeping with class justice, Donovan demonstrates that these juries, through their decisions, helped shape reform of the nation's criminal justice system.